Becoming Jane: the individuation represented by movie (Fractal: Journal of Psychology, 2009)
This is a explanatory work with the intent to establish a dialogue between the Julian Jarrold's movie Becoming Jane and the Jungian conception of the individuation process. It was observed that the movie makes many references to the Jung's work, being, the main plot, a perfect example (intentional or not) of the process of personal development, by the junguians known as individuation process. On the analyzed movie, the main character passes through the difficult process of discovering of one self. This is a very common experience which can be noted on many people's life and is essential to self realization.